If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5(x + -3) = -2 + 4x + -25 Reorder the terms: 2x + -5(-3 + x) = -2 + 4x + -25 2x + (-3 * -5 + x * -5) = -2 + 4x + -25 2x + (15 + -5x) = -2 + 4x + -25 Reorder the terms: 15 + 2x + -5x = -2 + 4x + -25 Combine like terms: 2x + -5x = -3x 15 + -3x = -2 + 4x + -25 Reorder the terms: 15 + -3x = -2 + -25 + 4x Combine like terms: -2 + -25 = -27 15 + -3x = -27 + 4x Solving 15 + -3x = -27 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 15 + -3x + -4x = -27 + 4x + -4x Combine like terms: -3x + -4x = -7x 15 + -7x = -27 + 4x + -4x Combine like terms: 4x + -4x = 0 15 + -7x = -27 + 0 15 + -7x = -27 Add '-15' to each side of the equation. 15 + -15 + -7x = -27 + -15 Combine like terms: 15 + -15 = 0 0 + -7x = -27 + -15 -7x = -27 + -15 Combine like terms: -27 + -15 = -42 -7x = -42 Divide each side by '-7'. x = 6 Simplifying x = 6
| 4(3z-2)=2(n+1) | | 5(12-2x)=3(7+5x) | | 8=4r+16 | | 7(y-9)+24=3(y-6) | | 13x-20-41=8x | | 6+8b=9b | | -100=-t/3-90 | | 90.47=.6x-54.31 | | x^2-12x+36=45 | | 5.49(43/4)= | | 8y-5(c+2)=7 | | 7r^3-7r=0 | | 24=-2(5-x)+4 | | -7.2q+1.8=-19.8 | | 10s^3-250s=0 | | 3(-9)=30 | | 54.31-.6=90.47 | | r^2=184 | | x+11+3x+1=180 | | 2(3+g)=-4(g+1) | | -8=-2(8x+5)-5(1-3x) | | 4+5x=7x-15 | | y=-x+14x-24 | | 3x+19+4x-2=180 | | 7+19m=35+12m | | 7.3+5.7=2x+4.7-1x | | 10r^3+40r=0 | | 7y=x+28 | | 8v^3-200v=0 | | 25t+5=25t | | 20+4x=44x | | 8(x-8)+6=-3x+8 |